Pengaruh Kepemimpinan dan Motivasi Kerja terhadap Komitmen Organisasional Pegawai Pusat Pendidikan Kelautan dan Perikanan - Suherman Suherman; Jono M Munandar; Sukiswo Dirdjosuparto (Jurnal Manajemen dan Organisasi, 2017)
Improving public sevice can be achieved by having employees who have high organizational commitment. The purpose of this research is to determine the effect of leadership style and work motivation to organizational commitment on employee of maritime affairs and fisheries education center. The effects were directed to diffrerentiate between transactional & transformational leadership. The sample in this reseach consist of 35 employee of maritime affairs an fisheries education center. The sampling used purposive sampling, data collection methods with questionaires. The data was processed by using Smart PLS with relation of reflective indicator at 95% confidence level. The result shows that the leadership is not significant enough to effect the organizational commitment. Leadership has significantly effect on work motivation, while work motivation has significantly effect on organizational commitment.